Macular Carotenoids and Cognitive Function in a Young Adult Population (FS05-07-19). (13th June 2019) - Ramirez, Christina; Lightfield, Katherine; Zuniga, Krystle
Abstract: Objectives: Improving cognitive health in young adulthood may improve academic and career success and prevent early age-related cognitive decline. A growing body of evidence suggests that the dietary carotenoid lutein may promote cognitive function; however, these studies have primarily been conducted in Non-Hispanic White populations. The objective of this study was to examine the relationship between macular pigment optical density (MPOD), a biomarker of lutein status, and cognitive function in a diverse, young adult population. Further, we examined the association between fruit and vegetable (F&V) intake and MPOD scores. Methods: In this cross-sectional study, seventy young adults (Mean = 20.2, SD = 2.3 years of age), were recruited from a university in Central Texas. Daily F&V intake were assessed by the NCI fruit and vegetable intake screener. MPOD was measured with heterochromatic flicker photometry. Cognitive performance was assessed with the NIH Toolbox Cognition Battery, and fully corrected T-scores that correct for age, gender, race/ethnicity, and education were used for analyses. Participants were split into Low and High MPOD groups based on the MPOD median of the sample. The association between F&V intake and MPOD was assessed by multiple linear regression, including body fat percentage as a covariate. F&V intake as a function of MPOD group was analyzed by ANOVA, and cognitive scores were compared using ANCOVA with BMI as a covariate. Results: The sample was primarily female (68.5%) and Caucasian (72.7%), and 40% of the population was Hispanic. The MPOD mean (Mean = 0.39, SD = 0.17) of the sample was above the reported national average of 0.33. Participants consumed approximately 1 cup of fruits and 1 cup of vegetables a day. F&V intake was not correlated with MPOD scores (R 2  = −0.03, P  = 0.81), and F&V intake did not significantly differ between High and Low MPOD groups. Episodic memory performance was significantly higher in the high MPOD group compared to those with low MPOD ( P  = 0.041). No other differences were found between the MPOD groups for the other fluid cognitive tests. Conclusions: MPOD was not a biomarker for F&V intake which may be due to the overall low intakes of these lutein-containing foods in the young adult sample. Lutein's cognitive benefits in young adults may be domain specific. Funding Sources: none.